2019
DOI: 10.1556/066.2019.48.1.15
|View full text |Cite
|
Sign up to set email alerts
|

Yield, quality, antioxidant, and sensorial properties of diced tomato as affected by genotype and industrial processing in Southern Italy

Abstract: Research was carried out on processing tomato in Southern Italy in order to compare four round-prismatic type hybrids oriented to diced produce (4420, Miceno, Nemabrix, Impact as a control). The hybrid Nemabrix attained the highest marketable yield (180.9 t ha–1), due to both the highest number of fruit per plant and their mean weight (103.7 and 70 g, respectively), and it was not significantly different from the other genotypes in terms of processing efficiency both as a total and along dicing chain (67.8% an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 21 publications
3
4
0
1
Order By: Relevance
“…The average content of total phenols in fresh and control (T1) were 836.3 and 579.7 mg/100g (DW), respectively, at zero time. These result are in agreement with (De Sio et al, 2019) who reported that compared to fresh fruit , diced tomatoes showed significantly reduced concentrations of polyphenols in terms of total solids (-8%). Pre-treated samples showed high maintained of total phenols during storage compared to control.…”
Section: Phytochemical Compounds and Antioxidant Activity Of Canned Tsupporting
confidence: 93%
See 1 more Smart Citation
“…The average content of total phenols in fresh and control (T1) were 836.3 and 579.7 mg/100g (DW), respectively, at zero time. These result are in agreement with (De Sio et al, 2019) who reported that compared to fresh fruit , diced tomatoes showed significantly reduced concentrations of polyphenols in terms of total solids (-8%). Pre-treated samples showed high maintained of total phenols during storage compared to control.…”
Section: Phytochemical Compounds and Antioxidant Activity Of Canned Tsupporting
confidence: 93%
“…The lowest lycopene content of sun-dried tomatoes could be due to the drying conditions they were exposed to light and oxygen. While (De Sio Jose et al, 2019) reported that, no significant differences between raw and diced tomatoes were recorded for lycopene on a fresh weight basis. On the other hand, control (T1) had the lowest contents of lycopene and total carotenoids compared with T2, T3 and T4, which may be due to the protective effect for pre-treatment for samples.…”
Section: Phytochemical Compounds and Antioxidant Activity Of Canned Tmentioning
confidence: 88%
“…Among the varieties compared, 'Yaltinsky 6А' showed the highest yield thanks to the highest mean bulb weight, though not significantly different from 'Kendy F1', 'Beam Promine' and 'Tropea' (Table 1); 'Yaltinsky rubin' had the worst performance (-35 % compared to the top production). The close relationship between yield and mean weight of the plant edible part has also been recorded in other species [De SIO et al, 2019] .…”
Section: Yield and Nutritional Propertiessupporting
confidence: 70%
“…The mineral elements were assessed according to Rouphael et al [35]. Lycopene determination was performed referring to De Sio et al [36]; total phenols and ascorbic acid, as described by Golubkina et al [37]. The antioxidant activity was assessed according to Brand-Williams et al [38].…”
Section: Determinations Of Fruit Quality Mineral Composition and Antmentioning
confidence: 99%